Intuition in Organizations: Implications for Strategic Management - Hodgkinson, Gerard P.; Sadler-Smith, Eugene; Burke, Lisa A.; Claxton, Guy; Sparrow, Paul R. (Long range planning, 2009)
Recent advances in social cognitive neuroscience and related fields have rejuvenated scholarly research into intuition. This article considers the implications of these developments for understanding managerial and organizational decision making. Over the past two decades, researchers have made considerable progress in distinguishing intuition from closely-related constructs such as instinct and insight and the interplay between these non-conscious forms of cognition and explicit reasoning processes is now better understood. In the wake of significant theoretical and methodological convergence centred on dual-process theories of reasoning, judgment and social cognition, supported by functional magnetic resonance imaging (fMRI) studies, several of the foundational assumptions underpinning classic theories and frameworks in strategic management and entrepreneurship research are being called into question. Old models based on a simplistic left brain/right brain dichotomy are giving way to more sophisticated conceptions, in which intuitive and analytical approaches to decision making are underpinned by complex neuropsychological systems. In the light of these advances, the authors offer their reflections on what this all means for the assessment, development and management of intuition in the workplace.